The origins of early Christian literature contextualizing the New Testament within Greco-Roman literary culture - Walsh, Robyn Faith 1980- (Cambridge, United Kingdom New York, NY, USA Port Melbourne, Australia New Delhi, India Singapore Cambridge University Press, 2021)
The Myth of Christian Origins -- The Romantic "Big Bang": German Romanticism and Inherited Methodology -- Authorship in Antiquity: Specialization & Social Formations -- Redescribing Early Christian Literature: The Gospels, The Satyrica, and Anonymous Sources -- The Gospels as Subversive Biography -- Conclusion.
"Conventional approaches to the Synoptic gospels argue that the gospel authors acted as literate spokespersons for their religious communities. Whether described as documenting intra-group "oral traditions" or preserving the collective perspectives of their fellow Christ-followers, these writers are treated as something akin to the Romantic Poet speaking for their Volk - a questionable framework inherited from 19th-century German Romanticism. In this book, Robyn Walsh argues that the Synoptic gospels were written by elite cultural producers working within a dynamic cadre of literate specialists, including persons who may or may not have been professed Christians. Comparing a range of ancient literature, her ground-breaking study demonstrates that the gospels are creative works produced by educated elites interested in Judean teachings, practices, and paradoxographical subjects in the aftermath of the Jewish War and in dialogue with the literature of their age. Walsh's study thus bridges the artificial divide between research on the Synoptic gospels and early Christianity"--
Literaturverzeichnis: Seite 201-221
Archivierung/Langzeitarchivierung gewährleistet
Keywords: Bible -- Criticism, interpretation, etc; Christian literature, Early -- History and criticism; Classical literature -- History and criticism; Christianity and literature -- History -- To 1500; Hochschulschrift